On scalar mesons from the combined analysis of multi-channel ππ scattering and J/ψ decays; International Journal of Modern Physics A; Vol. 26, iss. 3-4 - Surovtsev Yu. S.; Bydzovsk P.; Gutsche Th.; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich (2011, 2011)
Title screen